DAYA ANTIBAKTERI EKSTRAK ETANOL KEMBANG SEPATU (Hibiscus rosa sinensis L.) SEBAGAI ALTERNATIF BAHAN MEDIKAMEN SALURAN AKAR TERHADAP Enterococcus faecalis - Choirunnisa, Efika; Wibowo, Gustantyo Wahyu; Antari, Arlita Leniseptaria; Purnomo, Brigitta Natania Renata (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUND: Enterococcus faecalis is the dominant bacteria found in root canals, especially in failure of root canal treatment. Therefore, antibacterial agents are required as a means to achieve complete disinfection of the root canal system. One of the natural ingredients that has been proven to have antibacterial properties is the ethanol extract of hibiscus (H. rosa sinensis L.), so it has the potential to be used as a root canal medicament to inhibit growth and eliminate E. faecalis bacteria.   OBJECTIVE: Testing the effectiveness of hibiscus (H. rosa sinensis L.) ethanol extract as a potential root canal medicament. METHOD: The study was conducted using a true experimental post-test only control group design in 6 treatment groups with various concentrations of hibiscus extract (100%, 50%, 25%, 12.5%, 6.25, and 3.125%) and a positive control group. (Brain Heart Infusion added E. faecalis) and negative (Brain Heart Infusion). The extract was then diluted to the concentration used and added with 1.5x108CFU/ml E. faecalis and then cultured using the spread method on NA media, incubated anaerobically at 37oC for 24 hours, then the colonies that grew were counted using a colony counter. RESULT: The results showed that 100% concentration had the highest ability to inhibit the growth of E. faecalis bacteria (92.7%) with an average number of colonies growing of 4.4 x 102 CFU/ml. The minimum inhibitory concentration (MIC) was shown at a concentration of 50%, with an inhibiting ability of 90.17% and the average number of colonies that grew was 5.9 x103 CFU/ml. Kruskal Wallis statistical test showed a significant difference in the number of colonies (p<0.05). CONCLUSION: Hibiscus extract with a concentration of 100% has the highest ability to inhibit the growth of E. faecalis bacteria and MIC is present at a concentration of 50%.